Karelian Heritage in the Toponymy of the Pomor Coast of the White Sea - Irma Ivanovna Mullonen (Вопросы ономастики, 2024)
This publication presents findings from the collection and analysis of toponymic materials gathered during the 2023 expedition to the Pomor Coast of the White Sea. Karelian toponyms are featured here as a substrate element. Although they comprise only about 10% (approximately 300 names) of the total number of toponyms, they give the impression of a more substantial presence. This is primarily because they denote some of the most significant landmarks in the area, and also due to the prevalence of geographical terms in the local Pomor language derived from Karelian dialects. The specific distribution of terms such as kórga, índola, and sélga highlights the distinctive characteristics of the southern edge of the Pomor Coast, particularly the rural locality of Nyukhcha, which is connected to the Vygozero region. The study also discusses the gradual erosion of the Karelian layer in toponymy and the processes involved in adapting the original Karelian place names, which are often overlooked by researchers due to the difficulty in identifying them. One such process is folk etymological convergence, where a toponym is assimilated to a familiar Russian word, often with some phonetic changes (e.g., Gárye Lake > Gagárye Lake). This is a type of direct adaptation. Another adaptation pattern, calque or translation, is evident in the coexistence of pairs (or groups) of toponyms within a single micro-area, where one retains the original Karelian form, while the other is a translated version. This scenario has significant potential for etymological study. The paper suggests several such connections, including the name of Túmishche Island and the Kétmuksa River, which flows into the White sea near the island. Their joint analysis allowed the author to reconstruct the lost Russian term *tumishche (< Slavic *(s)tum-), meaning ‘shelter, a secluded place where one can hide or wait out bad weather’. This etymology is further supported by the river name Ketmuksa, which embodies the Balto-Fennic kätke- or Sami giet’k’ât, both meaning ‘hide, conceal’.